2014
DOI: 10.1155/2014/849720
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Chemokines in Breast Cancer Pathology and Its Possible Use as Therapeutic Targets

Abstract: Chemokines are small proteins that primarily regulate the traffic of leukocytes under homeostatic conditions and during specific immune responses. The chemokine-chemokine receptor system comprises almost 50 chemokines and approximately 20 chemokine receptors; thus, there is no unique ligand for each receptor and the binding of different chemokines to the same receptor might have disparate effects. Complicating the system further, these effects depend on the cellular milieu. In cancer, although chemokines are a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 54 publications
0
60
0
Order By: Relevance
“…33 The concomitant high expression of PD-1 ligands in these tumors, as supported by in situ evaluation of their expression in tumor specimens of HER2+ BCs that showed higher PD-L1 and PD-L2 positivity in TRAR-low compared to TRAR-high tumors, may represent one of the mechanisms exploited by tumors cells to evade immune control. Unlike the situation in patients with melanoma, in whom PD-L1 expression was described as being a negative feedback mechanism that followed CD8+ T cell infiltration and depended on their presence 34,35 the modulation of PD-1 ligands by HER2 signals that we demonstrated in BC cell lines suggests that in HER2+ BCs this immunosuppressive pathway is also directly orchestrated by cancer cells (i.e., innate immune evasion).…”
Section: Discussionmentioning
confidence: 87%
“…33 The concomitant high expression of PD-1 ligands in these tumors, as supported by in situ evaluation of their expression in tumor specimens of HER2+ BCs that showed higher PD-L1 and PD-L2 positivity in TRAR-low compared to TRAR-high tumors, may represent one of the mechanisms exploited by tumors cells to evade immune control. Unlike the situation in patients with melanoma, in whom PD-L1 expression was described as being a negative feedback mechanism that followed CD8+ T cell infiltration and depended on their presence 34,35 the modulation of PD-1 ligands by HER2 signals that we demonstrated in BC cell lines suggests that in HER2+ BCs this immunosuppressive pathway is also directly orchestrated by cancer cells (i.e., innate immune evasion).…”
Section: Discussionmentioning
confidence: 87%
“…It is reported that KV7.3 is expressed in osteoblast‐like cells and plays an important role in osteoblast differentiation through glutamatergic communication during matrix maturation and mineralization . Nabeshima et al and Krieger et al found that inhibitory mutant chemokines and antagonists of chemokine receptors promoted osteoblast differentiation, bone metastasis and bone formation . In addition, chemokines produced by the osteoblasts mediate the crosstalk between osteoblasts and osteoclasts to maintain bone remodelling .…”
Section: Discussionmentioning
confidence: 99%
“…These interactions are often mediated by chemokines and their receptors, many of which belong to the G-protein-coupled receptor (GPCR) family of receptors (2). In tumors, local production of chemokines plays an important role in attracting leukocytes and other inflammatory cells (3). Similarly, tumor cells express receptors that respond to chemokines secreted by stromal cells, tumor-associated macrophages, tumor-infiltrating leukocytes, as well as chemokines secreted by adjacent tumor cells or in an autocrine manner (2).…”
Section: Introductionmentioning
confidence: 99%